Pengembangan LKPD Berbasis RME Dengan Pendekatan Etnomatematika Pada Materi Garis dan Sudut - Oktavia, Lilis; Fatqurhohman, Fatqurhohman; AH, Nurul Imamah; Agustina, Lady (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
The aim of this research and development is to determine the quality of Student Worksheets (LKPD) based on Realistic Mathematics Education (RME) with an ethnomathematics approach as teaching materials that are suitable for use. This type of research is Research and Development (R&D) with a research model referring to the development of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this research are 7th grade students of SMP Muhammadiyah 9 Watukebo with a total of 121 participants/students (pilih salah satu aja). Three types of questionnaires were used in this research, such as; validation questionnaire sheet, teacher’s response questionnaire as the practicality assessment, and student’s response questionnaire as the effectiveness assessment for the LKPD. Results of the data analysis are (1) validation score from two validators on developed LKPD obtained an average score of 3.85 which categorized as valid, (2) the practicality score of two teachers on developed LKDP obtained a mean score of 4.75 which categorized as highly practical, (3) effectiveness score from the learners on developed LKPD obtained an average of 4.551 which categorized as highly effective. Thus, the Student Worksheet (LKPD) based on Realistic Mathematics Education (RME) with an ethnomathematics approach in line and angle material is suitable for use.